Mozambique Economic Update, December 2019 : Mind the Rural Investment Gap - World Bank (World Bank, Washington, DC, 2020)
As 2019 drew to a close, a year when Mozambique faced devastation caused by two severe cyclones, the country looks ahead having made significant progress in terms of economic stability, having strengthened its external buffers and having improved its fiscal position. The metical has been broadly stable since mid-2017, contributing to reduced inflationary pressures and providing room for an appropriately cautious monetary policy easing cycle. Growing investment flows, mostly linked to the extractive industries, have bolstered international reserves. Additional progress has been made in fiscal management with a notable reduction in the primary deficit between 2015 and 2018 and significant efforts to protect priority spending. Plus, with the progress to date in advancing its LNG interests, there is much to anticipate from the coming years. So, in this context and as the government enters a new term, where should the focus of policy makers be? The challenge remains to be growth. Growth was set further back in 2019 as Cyclones Idai and Kenneth and slower coal production affected output and is expected to fall to around 2.3 percent in 2019, down from 3.3 percent in 2018. With a population growth rate of 2.8 percent, this translates into a decline in the standard of living. Poverty has been further aggravated by the cyclones, which are likely to have impacted both the urban and rural poor in the affected areas. Growth is expected to accelerate with developments in the LNG sector and progress in post-cyclone reconstruction. But much of this expected growth is generated from the demand side of the economy, namely extractives-led investment and growing consumer demand, and less so from the supply side such as manufacturing, backbone services or non-extractive export growth. So, having put muchof the past economic volatility behind, structural reforms for more sustainable and inclusive growth must return to the center of the agenda, with the objective of recovering from the recent cyclones in the short-term and, in the medium term, of using the LNG opportunity to produce, export and employ.